Energy Security and Climate Change: India’s Responses to the Challenges - C. Vinodan (UUM Press, 2015)
Energy is the prominent navigator of climate change as it contributes to most of the greenhouse gases (GHGs) and the burning of fossil fuels are the foremost sources of GHG emissions. Climate change is a major challenge for developing countries like India that face large scale climate variability and are exposed to enhanced risks from climate change. Few countries in the world are as vulnerable to the effects of climate change as India is with its vast population that is dependent on the growth of its agrarian economy, its expansive coastal areas and the Himalayan region and islands. The vulnerabilities of climate change and energy insecurity are directing a global changeover towards a low carbon and sustainable energy path. In the UNFCC, India has cleared its stand that it would not make any commitments to trim down its GHG emissions as it has one of the least per capita emissions and in the fi rst place the developed world is responsible for the dilemma and the developing world requires the carbon space to spring up. But by being a responsible and progressive member of the international community, India demonstrated the flexibility towards the endeavours to trim down climate change causalities. India is endowed with diverse natural resources such as solar, wind, water and biomass; these are the promising resources to meet up the energy requirements of the coming years. The present paper attempts to analyse the linkages between climate change and energy security. The paper also aims to project India’s response to the global climate regime. The paper argues that the problems of climate change and energy security are the major obstacles for India’s energy policy while they open gargantuan opportunities to shift its people to cleaner energy trajectories and know-how in the long term.